School performance and behaviour change after adenoidectomy with myringotomy in children suffering from otitis media with effusion - Al-Masum, Syed Hasan Imam; Fakir, Abu Yousuf (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17414 Ibrahim Cardiac Med J 2012; 2(1): 27-31